Analisis Kualitas Proses Pembelajaran Melalui Penerapan Strategi Tandur Pada Konsep Sistem Ekskresi Manusia - Muhammad Arafah (Journal of Education and Teaching (JET), 2020)
This research was conducted based on the fact that students’ were less enthusiastic in participating in the learning process. This is due to the monotonous learning conditions. Therefore, the researchers assessed that teachers need to be assisted in designing innovative, attractive learning strategies that can activate students. The TANDUR learning strategy is designed together (researchers and teachers), and is applied in the learning process. The research data were processed using the percentage qualitative descriptive method. Learning activities with the TANDUR strategy that have been implemented have generally gone well. The results of data analysis and discussion show that the quality of learning outcomes in concept understanding is considered good (83.75), the quality of learning outcomes for scientific work is considered adequate (68.75, the quality of student activity is considered good (80.6) and the quality of teacher performance is considered very good ( 96.9) Of the four aspects that have been determined, the learning outcomes of the scientific work aspects have not been achieved optimally. The quality of the teaching and learning process that has taken place is considered good with a score of 78.9